Effects of Electrical Stress and High-Energy Electron Irradiation on the InGaP/GaAs Heterojunction Phototransistor. Issue 1792 (11th May 2015) - Than, Phuc Hong; Uchida, Kazuo; Makino, Takahiro; Ohshima, Takeshi; Nozaki, Shinji
ABSTRACT: In this paper, we discuss the characteristics of the InGaP/GaAs heterojunction phototransistors (HPTs) before and after the electrical stress at room temperature and assess the effectiveness of the emitter-ledge passivation. Although an electrical stress given to the phototransistors by keeping a collector current density of 37 A/cm 2 for 1 hour at room temperature was too small to affect the room-temperature common-emitter current gain and photocurrent of both HPTs with and without the emitter-ledge passivation, they showed a significant decrease at 420 K due to the room-temperature electrical stress. Nevertheless, the room-temperature common-emitter current gain and photocurrent of the HPT with the emitter-ledge passivation were still higher than those of the HPT without the emitter-ledge passivation. The effectiveness of the emitter-ledge passivation against the electrical stress was more significant than that on the current gain in the dark. In addition to the electrical stress experiment, for a potential application of the InGaP/GaAs HPTs in space, we will irradiate the HPTs with 1-MeV electrons at the Japan Atomic Energy Agency. Both current gain and photocurrent decreased significantly after the electron irradiation. In contrast to the electrical stress, the damage due to the high-energy electron irradiation is a bulk-related phenomenon, and the emitter-ledge passivation does not seem to suppress the degradation.